2021
DOI: 10.1002/hep4.1803
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of Telomere Length With Liver Disease and Mortality in the US Population

Abstract: Physiologic aging leads to attrition of telomeres and replicative senescence. An acceleration of this process has been hypothesized in the progression of chronic liver disease. We sought to examine the association of telomere length (TL) with liver disease and its impact on mortality risk. A cohort of 7,072 adults with leukocyte TL measurements from the National Health and Nutrition Examination Survey 1999-2002 with mortality follow-up through 2015 was analyzed. Liver disease was defined by aminotransferase le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(96 citation statements)
references
References 39 publications
2
94
0
Order By: Relevance
“…Heavy current drinkers were defined as ≥3 drinks per day for women and ≥4 drinks per day for men, with five or more binge drinking days per month; moderate drinkers were defined as ≥2 drinks per day for women and ≥3 drinks per day for men, with ≥2 binge drinking days per month. Light drinkers: did not meet the above criteria ( 11 , 12 ). In the US, PIR is defined as the ratio between a household's self-reported income and the poverty line.…”
Section: Methodsmentioning
confidence: 99%
“…Heavy current drinkers were defined as ≥3 drinks per day for women and ≥4 drinks per day for men, with five or more binge drinking days per month; moderate drinkers were defined as ≥2 drinks per day for women and ≥3 drinks per day for men, with ≥2 binge drinking days per month. Light drinkers: did not meet the above criteria ( 11 , 12 ). In the US, PIR is defined as the ratio between a household's self-reported income and the poverty line.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking more than 100 cigarettes in life and smoke not at all now were defined as former; the definition of now was smoking more than 100 cigarettes in life and smoking some days or every day (from the questionnaire in the database: smoked at least 100 cigarettes in life). The drink was divided into no, mild, moderate, and heavy as follows: heavy alcohol user: ≥3 drink times/day for women or ≥4 drink times/day for men or binge drinking on ≥5 days/month; moderate alcohol user: ≥2 drink times/day for women or ≥3 drink times/day for men or binge drinking ≥2 days/month; mild alcohol user: none of the above but drinking currently; and no was defined as never drinking ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…They found that men have shorter telomere lengths as compared to females. They also hypothesized that women have lower telomere attrition rates which could explain the lower mortality rates [ 29 ].…”
Section: Discussionmentioning
confidence: 99%